Hemin accumulation and identification of a heme‐binding protein clan in K562 cells by proteomic and computational analysis. Issue 2 (7th October 2021) - Tsolaki, Vasiliki‐Dimitra C.; Georgiou‐Siafis, Sofia K.; Tsamadou, Athina I.; Tsiftsoglou, Stefanos A.; Samiotaki, Martina; Panayotou, George; Tsiftsoglou, Asterios S.
Abstract: Heme (iron protoporphyrin IX) is an essential regulator conserved in all known organisms. We investigated the kinetics of intracellular accumulation of hemin (oxidized form) in human transformed proerythroid K562 cells using [ 14 C]‐hemin and observed that it is time and temperature‐dependent, affected by the presence of serum proteins, as well as the amphipathic/hydrophobic properties of hemin. Hemin‐uptake exhibited saturation kinetics as a function of the concentration added, suggesting the involvement of a carrier‐cell surface receptor‐mediated process. The majority of intracellular hemin accumulated in the cytoplasm, while a substantial portion entered the nucleus. Cytosolic proteins isolated by hemin‐agarose affinity column chromatography (HACC) were found to form stable complexes with [ 59 Fe]‐hemin. The HACC fractionation and Liquid chromatography‐mass spectrometry analysis of cytosolic, mitochondrial, and nuclear protein isolates from K562 cell extracts revealed the presence of a large number of hemin‐binding proteins (HeBPs) of diverse ontologies, including heat shock proteins, cytoskeletal proteins, enzymes, and signaling proteins such as actinin a4, mitogen‐activated protein kinase 1 as well as several others. The subsequent computational analysis of the identified HeBPs using HemoQuest confirmed the presence of various hemin/heme‐binding motifs [C(X)nC, H, Y] in their primary structures and conformations. The possibility that these HeBPs contribute to a heme intracellular trafficking protein network involved in the homeostatic regulation of the pool and overall functions of heme is discussed. Abstract : Indicating potential mechanisms of hemin uptake and distribution, as well as the several hemin‐binding proteins (HeBPs) identified in human pro‐erythroid K562 cells. Illustration of heme/hemin (He) transporters and HeBPs identified that act as potential heme traffickers and regulators of processes in various subcellular compartments. Added hemin or heme released during the hemolysis of disintegrated RBCs is transported intracellularly via different mechanisms involving: (a) The He–Hemopexin complex that is taken up by a CD91 receptor‐mediated endocytosis process; (b) a portion of heme is also taken up via human serum albumin through transferrin receptor, and (c) The Haptoglobin‐hemoglobin‐mediated CD163 uptake. Moreover, a portion of heme is transported by passive diffusion and another via still uncharacterized cell surface hemin‐receptor(s) (R). De novo synthesized heme in the mitochondria migrates into the intracellular heme pool. Part of this is exported out by the FLVCR1 protein and another is catabolized by heme oxygenase (HO)−1 and 2 to regulate the intracellular pool of heme and avoid heme‐induced damage. When inside, heme is transported into the nucleus, the mitochondria, and Golgi apparatus, via mechanisms of heme intracellular trafficking still under investigation. The proportion of the exogenously added hemin does not exceed 0.1%–0.2% of the total heme intracellular pool that usually ranges from 30 to 60 nM for nondifferentiated K562 cells. Heme transported into the nucleus interacts with specific G4 DNA motifs, and/or other regions such as MARE/ARE sequences at the promotors of genes encoding globin, HO‐1, and others where known transcription factors Nrf2 and Bach1 bind to. Heme and HBPs are shown in red. CD91 and CD163 cell surface antigens; EEF1A1, eukaryotic elongation factor 1A1; G4, G‐quadruplex DNA motif; He, Heme; Hpx, hemopexin; HNRNPK, Heterogeneous nuclear ribonucleoprotein K; HSA, human serum albumin; HO‐1, heme oxygenase‐1; HSPs, heat shock proteins; MAPK1, mitogen‐activated protein kinase‐1; R, heme receptor. Created with BioRender.com .